(3efGgd GdYQaGf hehQO GdXeBf HJMbjb hJHjjf LhGH SDGd eG GdEfSGfs - (3GdWQjfj, GdeGdcj, YHO GdLhGO Hf EHQGgje, (B1073 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3deG cGf Gdjhe GdKGfj ef TgQ TYHGf (B1041 (3hLeY ajg GdYdeGA hGdYXeGA hNdGUI GdNdGUI ef GdCYjGf ddJHQc HSeGY NJe HYV aVdGA gPG GdReGf ddbQBf (B...s
(3BNQgG (B:s
... (3gPG GdEdMGb dG VQQ Ydjg hdG VQGQ hdG JaJbQ HYO Pdc Edi HjGf hgPG SfM hXgQ dj hGdSdGe(B.s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2/50s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdJUha hGdBOGH GdTQYjIs